2019
DOI: 10.1001/jamanetworkopen.2018.7673
|View full text |Cite
|
Sign up to set email alerts
|

Association of Wearable Activity Monitors With Assessment of Daily Ambulation and Length of Stay Among Patients Undergoing Major Surgery

Abstract: This cohort study among patients undergoing major surgery defines the distribution of digitally measured daily step counts after major inpatient surgical procedures, assesses the accuracy of physician assessment and ordering of ambulation, and quantifies the association of digitally measured step count with postoperative length of stay in the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
149
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(154 citation statements)
references
References 19 publications
3
149
1
1
Order By: Relevance
“…While the devices were able to assess sleep as well as general activity, the integration and merging of data into existing care pathways and databases is more challenging. More recently, one group found patients with a higher post-operative daily step count were less likely to have a prolonged LOS, allowing prediction of those at risk of poor outcomes [42].…”
Section: Technology and Healthcarementioning
confidence: 99%
“…While the devices were able to assess sleep as well as general activity, the integration and merging of data into existing care pathways and databases is more challenging. More recently, one group found patients with a higher post-operative daily step count were less likely to have a prolonged LOS, allowing prediction of those at risk of poor outcomes [42].…”
Section: Technology and Healthcarementioning
confidence: 99%
“…A recent prospective study evaluated the association between daily ambulation measured by wearable activity monitors and LOS among patients undergoing major surgery (including RC). They found that higher step count (up to 1000 steps) on postoperative day 1 was associated with a lower probability of a prolonged LOS …”
Section: Postoperative Componentsmentioning
confidence: 99%
“…For future work, objective physical performance assessment tools, such as the liver frailty index 11,12 or personal fitness trackers, may be useful to study the impact of pretransplant performance. 13 Because these tools require patient participation and therefore are not Clinical Gastroenterology and Hepatology 2020;18:54-56 often easily evaluated in very sick hospitalized patients, these data would need to be gathered by performing routine outpatient performance measurements leading up to transplantation. This type of study was performed by Lai et al 14 in patients awaiting LT (not limited to ACLF).…”
mentioning
confidence: 99%